2015
DOI: 10.5433/1679-0359.2015v36n6sup2p4215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pFSH dose reduction on in vivo embryo production in Dorper ewes

Abstract: To evaluate the effect of pFSH dose on the in vivo embryo production of Dorper ewes in the semi-arid northeast of Brazil, 40 sheep females were distributed into two groups of 20 animals that received intravaginal CIDR for 14 days, and two days before device removal, they received one of the following treatments: in the FSH200 group, the ewes received 200 mg of pFSH; and in the FSH128 group, the ewes received a total of 128 mg in decreasing doses every 12 h. Beginning 12 h after the conclusion of the treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The gradual increase of CLs diameter during the early luteal phase observed in animals from G100 and G133 indicates adequate development of these structures based on the information brought by some authors (Gonzalez de Bulnes et al, ; Kraisoon et al, ), who described progressive increasing of luteal area and CL weight, respectively, until mid‐luteal phase in sheep. Conversely, animals which received 200 mg of pFSH presented an increase in the diameter of CLs only between Days 11–13 and then, reduction on Days 14 and 15.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The gradual increase of CLs diameter during the early luteal phase observed in animals from G100 and G133 indicates adequate development of these structures based on the information brought by some authors (Gonzalez de Bulnes et al, ; Kraisoon et al, ), who described progressive increasing of luteal area and CL weight, respectively, until mid‐luteal phase in sheep. Conversely, animals which received 200 mg of pFSH presented an increase in the diameter of CLs only between Days 11–13 and then, reduction on Days 14 and 15.…”
Section: Discussionmentioning
confidence: 86%
“…From these findings, it can be expected that the production of embryos can be favoured when the lowest dose of pFSH is used. Although more studies are needed to confirm our hypothesis, the number of ovulations is decisive for the embryo yields as well as the luteal dynamic, especially the adequate progesterone concentrations until embryo collection day are beneficial to the uterine environment and embryonic development in donor females (Connell et al, ; Kraisoon et al, ). Brasil et al () observed a similar number of CLs to that obtained in this study using 133 mg of total dose of pFSH in Santa Inês ewes.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations